Long-term impacts of COVID-19 on stress and depression among teachers: Differences by gender - Huseth-Zosel, Andrea; Crary, Sarah L.; Orr, Megan (Journal of Teaching and Learning, 2024)
This article explores the impact of changes in teaching modalities resulting from the COVID-19 pandemic on the mental health of K-12 teachers, by gender, during the first year of the pandemic. Teachers from a random sample of K-12 schools in North Dakota and Minnesota were surveyed in April 2020, October 2020, and March/April 2021 about their current levels of stress and depression, as well as the frequency with which they experienced certain physical conditions. One-way analysis of variance and multiple regression were used to compare time points for each of the outcomes by gender. Female teachers were more likely to experience higher levels of stress than male teachers, while male teachers were more likely to experience higher levels of depression than female teachers, with spikes in stress and depression levels experienced by both males and females in Time 2. Additionally, physical symptoms were more likely to be experienced by female teachers, with Time 2 respondents overall reporting significantly higher proportions of physical symptoms than Time 1 or Time 3 respondents. Consistently experiencing heightened levels of stress and depression can lead to burnout for teachers. School districts need to monitor stress, especially among females, and depression, especially among males, to recognize the difference in experience for each gender in the teaching profession, as well as provide supports and resources to their teachers to help them in coping with these mental-health issues.